Photoinduced Electrocatalysis on 3D Flexible OsOx Quantum Dots. Issue 18 (15th March 2021) - Du, Yuncheng; Xue, Yurui; Zhang, Chao; Liu, Yuxin; Fang, Yan; Xing, Chengyu; He, Feng; Li, Yuliang
Abstract: Synthesizing active and durable catalysts for the hydrogen evolution reaction (HER) is of great significance for the development of a sustainable hydrogen economy. In this paper, an OsO x quantum dot loaded in 3D flexible graphdiyne is reported for photoelectrocatalysis, which shows greatly improved HER activity under light induction. The calculated and experimental results indicate graphdiyne (GDY) is not only used as the hole transfer layer to prevent hole–electron recombination, but can induce charge transfer for more high‐coordination osmium (Os 4+ ). Upon exposure to a Xe lamp, OsO x QDs/GDY shows greatly enhanced catalytic activities and stabilities under alkaline conditions. Significantly, GDY can promote the good distribution and stability of metal oxide quantum dots. The fundamental advantage of the OsO x QDs/GDY catalyst is to promote hole transport and generate a large number of active sites and its superior photocurrent performance and photo/electrocatalytic activity. Simultaneously, due to the unique properties of the internal electronic structure of the GDY, the Mott‐Schottky effect is promoted efficiently and as a typical semiconductor catalyst, OsO x QDs/GDY shows unparalleled performance. Abstract : Highly uniform and dispersed osmium oxide quantum dots grown on graphdiyne (GDY) are realized. The obtained catalyst shows highly active and durable electrocatalytic hydrogen evolution reaction performance under induction. GDY can effectively prevent hole–electron recombination and facilitate the charge transfer for greatly enhanced catalytic activities and stabilities under alkaline conditions.